The Effect of First Aid Training on Scout Members’ Knowledge of Everyday Emergencies at MAN 1 Serang - Anggun Elsana Putri; Lukmanulhakim Lukmanulhakim (Manajemen Pelayanan Kesehatan, 2026)
School environments are vulnerable to emergency incidents such as falls, bleeding, fractures, burns, and choking. Delays in providing first aid often occur because students lack adequate knowledge and skills to perform initial emergency management. Scout members are expected to become the first responders in schools; however, not all of them have received structured First Aid training. This study aimed to analyze the effect of First Aid training on the knowledge of Scout members regarding daily emergency management at MA Negeri 1 Serang. This study employed a quasi-experimental design using a pretest-posttest with control group approach. A total of 60 Scout members participated and were divided into intervention and control groups. Data were collected using a 35-item knowledge questionnaire with a Guttman scale. The Wilcoxon test was used to analyze changes within groups, while the Mann-Whitney test compared posttest scores between groups. The intervention group experienced a statistically significant improvement in knowledge after receiving First Aid training (p<0.001), whereas no significant improvement was observed in the control group. Furthermore, posttest knowledge scores in the intervention group were significantly higher than those in the control group. First Aid training effectively improves the knowledge of Scout members regarding daily emergency management. Therefore, integrating First Aid training into Scout extracurricular activities is recommended to strengthen emergency preparedness in schools.